Application of Thermostable Wheat Arabino-xylanase Xyn11A for Quality Improvement of Wholewheat Bread - Yuxi ZHANG; Xingyu LIU; Xiaoya QI; Huan RAO; Dandan ZHAO; Jianxiong HAO; Xueqiang LIU (Shipin gongye ke-ji)
The high cell-density fermentation production of thermostable arabino-xylanase Xyn11A and its application in the whole wheat bread quality improvement were investigated. The high cell-density fermentation method was used to produce Xyn11A, and its effect in whole wheat bread quality improvement was evaluated by determining the pasting characteristics, rheological properties, specific volume, texture, differential scanning calorimeter (DSC) and scanning electron microscopy (SEM). The results showed that the supernatant xylanase enzyme activity was 1884 U/mL after fermentation of recombinant Pichia pastoris in a 5-L fermenter for 108 h. Pioneering the application of wheat arabinoxylanase Xyn11A in whole wheat dough, the gelatinization characteristics showed that with the addition of Xyn11A, the peak viscosity, trough viscosity, and final viscosity exhibited a trend of initially decreasing and then increasing. Rheological properties indicated that with varying amounts of Xyn11A added (0 to 6 mg/kg), the extensibility of the dough increased from 173 mm to 181.5 mm. The Mixolab measurements revealed that the dough's C1 (maximum dough consistency), C2 (gluten weakening trough), C3 (peak viscosity), C4 (retained viscosity), and C5-C4 (starch retrogradation rate) decreased from 1.119, 0.443, 1.568, 1.399, 0.963 Nm to 1.113, 0.437, 1.512, 1.252, 0.774 Nm, respectively. The wheat arabino-xylanase Xyn11A was further applied in whole wheat bread, and the specific volume of whole wheat bread showed a tendency to increase and then decrease, and the hardness showed a tendency to decrease and then increase, and the best effect was achieved when the addition amount was 6 mg/kg, which increased the specific volume of the whole wheat bread by 15.6%, and the hardness decreased by 26% compared with the control group without Xyn11A. Addition 6 mg/kg of Xyn11A in whole wheat bread, the hardness of bread decreased in a range of 19.4%~23.9% at 4 ℃ for different storage time (1~5 d), indicating the enzyme could delay the aging speed. DSC showed that the melting temperature as well as the differential scanning calorimetric integral enthalpy decreased with the addition of 6 mg/kg Xyn11A compared with the control group without Xyn11A, indicating that the addition of Xyn11A delayed the aging of whole wheat bread. SEM results showed that the addition of Xyn11A resulted in a more continuous dough microstructure and a denser and more homogeneous internal mesh of the bread. In summary, wheat arabinoxylanase Xyn11A would show excellent effects in improving the quality of whole wheat bread and delaying the staling process, demonstrating good potential in the modification of baked goods.